2019
DOI: 10.48550/arxiv.1909.03604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive Sketch-and-Project Methods for Solving Linear Systems

Abstract: We present new adaptive sampling rules for the sketch-and-project method for solving linear systems. To deduce our new sampling rules, we first show how the progress of one step of the sketch-and-project method depends directly on a sketched residual. Based on this insight, we derive a 1) max-distance sampling rule, by sampling the sketch with the largest sketched residual 2) a proportional sampling rule, by sampling proportional to the sketched residual, and finally 3) a capped sampling rule. The capped sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Related Results. This result is related to recent work of Gower, Molitor, Moorman and Needell [11] who discuss non-uniform selection probabilities in the more general framework of Sketch-and-Project methods. In particular, their §7.4.…”
Section: 3supporting
confidence: 65%
See 1 more Smart Citation
“…Related Results. This result is related to recent work of Gower, Molitor, Moorman and Needell [11] who discuss non-uniform selection probabilities in the more general framework of Sketch-and-Project methods. In particular, their §7.4.…”
Section: 3supporting
confidence: 65%
“…discusses the convergence rate of the algorithm considered here for p = 1. The case p = ∞ has been studied by a large number of people; we emphasize the results of Nutini, Sepehey, Laradji, Schmidt, Koepke, Virani [29] and to references in [11].…”
Section: 3mentioning
confidence: 99%
“…, the Projection onto Convex Sets Method[2,6,7,11,36] and the Randomized Kaczmarz method[8,9,13,15,14,22,23,24,26,27,29,30,31,32,33,34,35,37,38,39,40,41,42].Strohmer & Vershynin …”
mentioning
confidence: 99%
“…They showed that as the number of threads increases, the rate of convergence improves and the convergence horizon for inconsistent systems decreases. Another more general class of block methods are sketch-and-project methods [4]. For a linear system Ax = b, sketch-and-project methods iteratively project the current iterate onto the solution space of a sketched subsystem S T Ax = S T b.…”
Section: Related Workmentioning
confidence: 99%